A novel all-natural (collagen+pectin)/chitosan aqueous two-phase microcapsule with improved anthocyanin loading capacity. (January 2023) - Jiang, Zhenyang; Zhao, Shaojie; Fan, Zhiying; Zhao, Chengying; Zhang, Lin; Liu, Dan; Bao, Yuming; Zheng, Jinkai
Abstract: Microcapsules based on an aqueous two-phase system (ATPS) have attracted increasing interest due to their all-aqueous biocompatible microenvironment, but the undesirable use of high concentrations of synthetic poly(ethylene glycol) and dextran (Dex) in conventional ATPSs has severely hindered their application in the food industry. In this study, a new type of ATPS microcapsule was developed by taking advantage of the spontaneous phase separation and simultaneous interfacial self-assembly of natural pectin, chitosan, and collagen. Chitosan (1 wt%) and collagen (4 wt%)+pectin (0.5 wt%) were used to form ATPS to replace poly(ethylene glycol) (15∼30 wt%) and Dex (15∼20 wt%) in conventional ATPSs. The (collagen + pectin)/chitosan microcapsules exhibited the plumpest morphology and highest stability at pH 6, and the smoothest interfacial membrane texture was achieved through interfacial self-assembly of pectin, chitosan, and collagen via electrostatic interactions and hydrogen bonds. Notably, anthocyanin could be stabilized by pectin in the inner phase, and the (collagen + pectin)/chitosan microcapsules had an improved anthocyanin encapsulation efficiency and loading capacity of 92.58% and 12.34 g/100 g, respectively, which was attributed to the electrostatic attractions between the flavylium cation form of anthocyanin and anionic pectin. This study yielded a strategy for constructing a new type of food-grade ATPS microcapsule using all-natural polysaccharides and proteins, and provided a novel all-aqueous template for loading hydrophilic bioactive components. Graphical abstract: Image 1 Highlights: Natural chitosan and collagen + pectin generate a spontaneous aqueous two-phase system. The novel (collagen + pectin)/chitosan microcapsules developed were stable at pH 6. Chitosan, pectin, and collagen could be self-assembled at the microcapsule interface. Anthocyanin could be stabilized by pectin in the inner phase via electrostatic attraction. (Collagen + pectin)/chitosan microcapsules had excellent anthocyanin loading capacity.